Analisis Kesulitan Membaca Permulaan Siswa Kelas 1 SD Negeri Grujugan Pamekasan - Rohmah, Mamluatur; Setyawan, Agung; Citrawati, Tyasmiarni (Lembaga Citra Pustaka, 2024)
This study aims to analyze the process and results of initial reading difficulties among grade 1 students at Grujugan State Elementary School. The research employs a descriptive method with a quantitative approach. The population consists of grade 1 students, and the sampling technique used is purposive sampling, selected based on specific criteria. Data collection methods include tests, observation, and documentation, while data analysis is conducted using non-statistical techniques. The research reveals that students face significant challenges in early reading stages. The highest difficulties occur in reading meaningless words, followed by challenges in reading fluency, reading aloud, and reading comprehension. Other observed difficulties include issues in word recognition, letter identification, and listening comprehension. Students’ specific characteristics of reading difficulties include letter confusion, reversing or changing words, skipping letters, incorrect word pronunciation, ignoring punctuation, and lack of comprehension and concentration. This study concludes that initial reading difficulties are multifaceted and require targeted interventions focusing on improving letter and word recognition, reading fluency, and comprehension to enhance students' reading abilities.